Development Chitosan-based forward Osmosis Membranes for Emergency Drinking Water Supply - Saiful Saiful; Ulfa Riana; Marlina Marlina; Muliadi Ramli; Nizar Mahmud (Graduate Program of Syiah Kuala University, 2018)
Development of forward osmosis (FO) membranes became one of the alternative methods for drinking water supply in an emergency. In this research, drinking water bags based on FO membrane have been developed using chitosan as the basic material of membrane. The chitosan membrane used for the manufacture of drinking water bags has a thickness of 0.043 mm, 30.3% porosity, tensile strength 28.83 kgf / mm2, swelling degree 43.5% and elongation of 7.16%. Drinking water bags are made with a combination of Polypropylene Plastic (PP) and aluminum foil with FO membrane inside. This drinking water bag can be applied for brackish water purification to be energy drinking water as one of the solutions for the drinking water supply in emergencies. FO process testing is done by using variation of sugar solution as the draw solution, that are glucose, fructose, sucrose and mixture. The concentration of applied draw solution is 1, 2 and 3M within 1 hour treatment. The highest water flux was obtained in 3M sucrose solution with a flux value of 5.25 L/m2hour. The results of drinking water quality parameters analysis in the form of pH, Total Dissolve Solid (TDS), salinity, conductivity, heavy metals and Escherichia coli (E. coli) contents showed that the FO water produc meets drinking water quality standards based on Indonesian government regulation of drinking water quality. FO-membrane-based drinking water bags are potentially used as an alternative solution for the energy drinking water supply in an emergency.